ANALISIS KADAR VITAMIN C PADA DAGING BUAH DURIAN MAMUJU (DURIO ZIBETHINUS MURR) SECARA KUALITATIF DAN KUANTITATIF - Hamzah, Aminah (Jurnal Ilmiah As-Syifaa, 2012)
Have been conducted by a obstetrical research of vitamin C at durio meat of Mamuju by qualitative and quantitatif.. The research aim to determine of vitamin C from durio meat of Mamuju by qualitative and quantitatif.Firstly fruit of durio are separated by their seed then it weighed that it enchanced by oxxilate acid 0.4 % and that it blended and filtered. Fitrat obtained to qualitative analyze by using the react FeCl3, Fehling and rate determined quantitatively vitamin C using the spectrophotometry UV-Visible at wave legth 516 nm obrtained rate of mean vitamin C that is durio meat of Mamuju 65.42 mg/100 g.Key Words : Durio Zibethinus Murr, Analysis, Vitamin C, qualitative and quantitatif.